4Arts Performing Arts Education Festival. - Black Swan State Theatre Company; West Australian Ballet Company; West Australian Symphony Orchestra; West Australian Opera ([Perth] : Black Swan State Theatre Company ; West Australian Ballet ; West Australian Symphony Orchestra ; West Australian Opera, 2012)
Advertisement for the 4Arts Performing Arts Education Festival, 14-15 June 2012, State Theatre Centre of WA. "Theatre, ballet, music and opera for students under one roof at the State Theatre Centre of WA! Free event for students and teachers from K-12." "Two vibrant days of performances & workshops." Features images representing the companies involved in the festival set aginst a grid paper background. From left to right the image includes: stairway of the State Theatre Centre, a cartoon cloud, series of 4 instant portraits of a man, a man holding a rapier and a copy of Thomas Papathanassiou's "Looming the memory"; a ballerina showering stars on a pair of pointe shoes; a cellist wearing a WASO shirt standing next to a music stand and the bust of a composer; an female opera singer holding a bunch of red roses, a pair of opera glasses and the exterior of the State Theatre Centre of Western Australia. "Proudly supported by Lotterywest, State Theatre Centre of Western Australia, Government of Western Australia, Department of Culture and the Arts, Department of Education, ArtsEdge, Black Swan State Theatre Company, West Australian Ballet, West Australian Symphony Orchestra, West Australian Opera"--at foot of poster.
Caption title.
National Library of Australia's copy previously folded, shows vertical and horizontal fold marks.
Keywords: Black Swan State Theatre Company -- Posters; West Australian Ballet Company -- Posters; West Australian Symphony Orchestra -- Posters; West Australian Opera -- Posters; Performing arts -- Study and teaching -- Activity programs -- Western Australia -- Posters; Posters, Australian; Australia -- Posters; Australian